The Effects of Protective Sensation on Functional Capacity, Peripheral Muscle Strength, and Balance in Patients with Type 2 Diabetes Mellitus - Usul M.; ÖZYILMAZ S.; TUNÇ M.; TOLUK Ö. (My University, 2026)
Background: Diabetes-related foot complications are among the most common complications in individuals with type 2 diabetes mellitus. The prevention of foot problems that are at risk of developing because of type 2 diabetes mellitus should be addressed within the framework of preventive approaches prior to treatment. The aim of this study was to evaluate protective sensation in people with type 2 diabetes mellitus who have not been diagnosed with early diabetes-related foot complications and to investigate the effects of protective sensation on peripheral muscle strength, balance, and functional capacity. Methods: This study included 42 volunteer patients (56.71 ± 7.59 years) who were followed up with a diagnosis of type 2 diabetes mellitus and met the inclusion criteria. Individuals were evaluated prospectively and via face-to-face interviews. Light-touch, vibration, and discrimination sense was evaluated to determine protective sensation. Peripheral muscle strength (quadriceps femoris, biceps brachii, and hand grip) was measured and a 6 min walking test for functional capacity and balance evaluation were performed. Spearman correlation analysis was conducted using SPSS Statistics 21.0 for data analysis. Results: At least one of the components of protective sensation was moderately correlated with peripheral muscle strength, functional capacity, and balance scores. Reduced protective sensation was also observed in individuals with type 2 diabetes mellitus without neuropathy. Conclusions: In type 2 diabetes mellitus patients, decreases in light-touch, vibration, and discrimination sense are moderately associated with parameters of peripheral muscle strength, functional capacity, and balance. In patients with type 2 diabetes mellitus, early foot sole sensory examination may prevent the development of neuropathy and support clinicians in early diagnosis.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Orthopedics and Traumatology; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Ortopedi; Clinical Medicine (Med); Clinical Medicine; Orthopedics; Ayak Bakımı; Ortopedi ve Spor Hekimliği; Podiatry; Orthopedics and Sports Medicine; diabetes complications; diabetic neuropathy; sensory functions